Sorotan Kajian Literatur Bersistematik: Manhaj Akidah, Fiqah dan Tasawuf Tarekat Aḥmadiyyah Sayyid Aḥmad Ibn Idrīs: A Systematic Literature Review: The Doctrinal Approaches of Creed, Jurisprudence and Sufism in the Aḥmadiyyah Ṭarīqah of Sayyid Aḥmad Ibn Idrīs - Ahmad Syahmi Ahmad Mohtari Yasim; Syed Mohammad Hilmi Syed Abdul Rahman (Al-Basirah Journal, 2024)
This article examines the creed, jurisprudence, and sufism methodology of the Aḥmadiyyah Order pioneered by Sayyid Aḥmad ibn Idrīs. His unique stance on these aspects distinguishes him from other ṭarīqah. Thus, he is known as a Reformist figure for his efforts in reforming several doctrines traditionally adhered to by previous ṭarīqahs. Consequently, this research aims to review existing literature to identify the methodology of this order. The research methodology employs the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) approach to ensure a systematic literature screening process. A total of nine past literatures have been selected for analysis. The findings indicate that Ibn Idrīs inclined towards the Salaf creed, while in terms of jurisprudence, he adhered to the Mālikī school in matters of customs and the Muḥaddithīn school in matters of worship. In terms of sufism, he pioneered the Aḥmadiyyah Ṭarīqah as a path to achieving the essence of sufism. His principles have become a guiding light for the followers of the Aḥmadiyyah Order, as he is its pioneer. These findings demonstrate that the innovations introduced by him have enriched the Islamic scholarly and spiritual heritage and broadened the spectrum of Sufi understanding and practice within the Sufi tradition.